Pulmonary Enteric Adenocarcinoma in a Super‐Elderly Patient: A Case Report and Literature Review - Akira Shimamoto; Natsumi Kojo; Haruko Saiki; Akinobu Hayashi; Motoshi Takao (Respirology Case Reports)
ABSTRACT Pulmonary enteric adenocarcinoma (PEAC) is an extremely rare subtype of non‐small cell lung cancer, characterised by histopathological features that resemble colorectal adenocarcinoma. Here, we report a case of PEAC in an 85‐year‐old male who presented with a pulmonary nodule initially identified at the age of 76. Initial PET‐CT (maximum standardised uptake value [SUVmax] = 2.8) was inconclusive, leading to strict follow‐up. Over 9 years, the nodule enlarged significantly (3.2 cm, SUVmax = 8.4). A transbronchial biopsy confirmed adenocarcinoma, and the patient underwent successfully video‐assisted thoracoscopic surgery with lymph node dissection. The histopathological analysis revealed CK7 and CK20 positivity, focal CDX2 positivity, and TTF‐1 negativity, confirming PEAC. Despite advanced age, the patient tolerated surgery well without adjuvant therapy. At the one‐year postoperative follow‐up, he remained disease‐free. This case emphasises the diagnostic utility of immunohistochemistry and the feasibility of surgical management, even in super‐elderly patients with PEAC.